2008
DOI: 10.1029/2007wr006371
|View full text |Cite
|
Sign up to set email alerts
|

Transient soil‐moisture dynamics and climate change in Mediterranean ecosystems

Abstract: [1] Plants in Mediterranean ecosystems have developed different strategies to cope with transient soil-moisture dynamics induced by the markedly out of phase seasonal behavior of rainfall and temperature. Deep-rooted plants use the soil moisture stored in the wet winter (extensive users), while shallower rooted plants exploit both the wet season storage and the more sporadic growing season rainfall (intensive users). Using stochastic models of soil-moisture dynamics, we present an analytical and numerical desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 49 publications
(65 reference statements)
0
76
0
Order By: Relevance
“…Plants with deeper roots may respond to infrequent heavy rainfall events rather differently and may not benefit from short-term changes in soil moisture in the upper soil layers in the way predicted by Knapp et al's model. In fact, the response of vegetation to rain events is likely to be highly dependent on plant life form, which is itself a function of climate and soil conditions (Sala and Lauenroth, 1985;Schenk and Jackson, 2002;Ogle and Reynolds, 2004;Viola et al, 2008). In dry climates, Porporato et al (2001) found that there is an intermediate rainfall frequency at which drought stress is minimum, and that this optimal frequency depends on plant and soil properties (see also Laio et al, 2001).…”
Section: Rainfall Variability and Ecosystem Fluxesmentioning
confidence: 99%
“…Plants with deeper roots may respond to infrequent heavy rainfall events rather differently and may not benefit from short-term changes in soil moisture in the upper soil layers in the way predicted by Knapp et al's model. In fact, the response of vegetation to rain events is likely to be highly dependent on plant life form, which is itself a function of climate and soil conditions (Sala and Lauenroth, 1985;Schenk and Jackson, 2002;Ogle and Reynolds, 2004;Viola et al, 2008). In dry climates, Porporato et al (2001) found that there is an intermediate rainfall frequency at which drought stress is minimum, and that this optimal frequency depends on plant and soil properties (see also Laio et al, 2001).…”
Section: Rainfall Variability and Ecosystem Fluxesmentioning
confidence: 99%
“…Am., 2008). The field capacity concept was originally introduced for irrigation scheduling purposes under a simplistic view of soil water movement in the SVA system (Veihmeyer and Hendrickson, 1927). It was soon used also by hydrologists who defined it as the maximum quantity of water that can be permanently retained in the soil against the pull of gravity (Horton, 1935).…”
Section: Techniques For Determining Field Capacitymentioning
confidence: 99%
“…Indeed, the full solution to the stochastic differential equation (2.1), p t (x), is available when constant parameters are assumed for this case [13]. However, because these assumptions do not place an upper bound on the value of x t , they also result in significant overestimation of x t when there is leakage or run-off.…”
mentioning
confidence: 99%
“…However, because these assumptions do not place an upper bound on the value of x t , they also result in significant overestimation of x t when there is leakage or run-off. Other implications for soil moisture and plant water stress are extensively discussed in reference [13] under constant climate conditions for the growing season. The next three cases are newer improvements on equation (2.5) that approximate LQ t using various assumptions for p t (x).…”
mentioning
confidence: 99%
See 1 more Smart Citation